The US as the "demander of last resort" and its implications on China's current account - Joshua Aizenman; Yothin Jinjarak (University of California, Economics Department, 2008)
This paper evaluates the degree to which current account patterns are explained by the variables suggested by the literature, and reflects on possible future patterns. We start with panel regressions explaining the current account of 69 countries during 1981-2006. We identify an asymmetric effect of the US as the 'demander of last resort': a 1% increase in the lagged US imports/GDP is associated with 0.3% increase of current account surpluses of countries running surpluses, but with insignificant changes of current account deficits of countries running deficits. Overall, the panel regressions account for not more than 4/5 of the variation. We apply the regression results to assess China's current account over the next six years, projecting a large drop in its account/GDP surpluses.
Keywords: F15; F32; 330; current account; demander of last resort; global balances; Zahlungsbilanzungleichgewicht; Prognose; Schätzung; Welt; China; USA